THE INFLUENCE OF DRUGS WITH IMMUNO-CORRECTIVE AND BIOCIDAL EFFECTS DURING THE CULTIVATION OF BROILER CHICKENS ON THE MORPHOFUNCTIONAL STATE OF ORGANS - Прилипко, Татьяна; Чечет, О.; Ложкіна, О.В.; Вячеслав, Коваленко; Марія, Купневська; Литвиненко, Сергій (SWorldJournal, 2024)
The results of the study of drugs with immuno-corrective and biocidal effects, which can be effectively used in the conditions of poultry farming, are presented. It was established that in experimental birds, the combined use of the symbiotic drug "Biomag